Burden of intimate partner violence, mental health issues, and help-seeking behaviors among women in Nepal - Monna Kurvinen; Anna Mia Ekström; Keshab Deuba (Women's Health)
Background: Intimate partner violence (IPV) is the most common form of violence, presenting a significant public health concern, especially for women and girls. Help-seeking can reduce future IPV and mitigate adverse health outcomes, including mental health issues. Objectives: This study is the first national assessment on IPV, mental health consequences, and associated help-seeking behaviors in Nepal. Design: A cross-sectional descriptive study. Methods: Using secondary data from the 2022 Nepal Demographic and Health Survey, this study includes 5178 women aged 15–49 and employs multivariate regression analysis to explore the association between IPV and mental health problems, as well as factors influencing help-seeking behavior for both issues. Results: Among participants, 31.4% reported ever experiencing IPV, and most (29.4% of all women) in the past 12 months. Of those ever experiencing IPV, 72.0% had not sought help for IPV, and 92.2% of those who did, opted for informal support. A total of 27.6% ( n  = 1427) of female interviewees reported anxiety symptoms, 21.5% ( n  = 1110) depressive symptoms, and 7.1% ( n  = 368) suicidal ideation within the past 2 weeks. These rates were higher among women who had experienced IPV in the past 12 months, with 41.1% reporting anxiety, 33.2% depression symptoms, and 14.1% suicidal ideation. Of the 4194 respondents with symptoms of anxiety, depression, or suicidal ideation who were asked about help-seeking for mental health issues, 19.4% ( n  = 812) had sought help, primarily from informal sources (93.4%, n  = 759). Emotional IPV in the past 12 months increased the odds of anxiety (adjusted odds ratio (aOR) 3.00, 95% confidence interval (CI) 2.08–4.31), depression (aOR 3.09, 95% CI 2.19–4.37), and suicidal ideation (aOR 1.91, 95% CI 1.20–3.04). Sexual IPV increased the odds of anxiety (aOR 2.88, 95% CI 1.67–4.95) and depression (aOR 2.12, 95% CI 1.32–3.41), while controlling behavior heightened the odds of depression (aOR 2.42, 95% CI 2.02–2.89) and suicidal ideation (aOR 2.24, 95% CI 1.25–4.02). Conclusion: This nationwide study reveals a high prevalence of IPV and related mental health problems among women in Nepal and a low rate of help-seeking behavior, in particular to formal support structures. Stronger health system responses and empowering informal support are essential to improve referrals and raise awareness for violence survivors.